OUTSOURCING AS A STRATEGIC OPTION TO ORGANIZATIONAL EFFECTIVENESS: A STUDY OF SELECTED MICRO-FINANCE BANKS IN SOUTHEAST NIGERIA - (Ph.D), ISAH ADAMU; CHUWUDI, CHIKWE, GODDEY; -DADDIE, JOEL AUGUSTUS (IJRDO - Journal of Applied Management Science, 2017)
this paper focused on outsourcing as a strategic option to organizational effectivenesswith selected micro-finance banks in south-east Nigeria as its study firms. From a population of578 members of staff from the selected microfinance, purposive sampling was used to select 410members of staff who were surveyed for the study. In line with the design of this study, the datacollected for this study was analyzed using inferential statistics. The study was guided by threeresearch objectives and hypotheses which are consistent. Data was gathered using a five pointlikert scale questionnaire and the hypotheses were tested using Mann-Whitney Test (U) using the20.0 version of statistical package for social sciences (SPSS). . It is concluded in this study thatmicro-finance banks in south-east Nigeria can leverage on outsourcing to improve theiradaptability, innovativeness and sustainability which are the hallmarks of improvedcompetitiveness and at the long-run organizational effectiveness. The researchers recommend thatmicro-finance banks should focus more on its core duties where it enjoys unique competitivecapabilities (UCC), while outsourcing its non-core functions. It should however, integrateoutsourcing programmes into the corporate strategy of the organization to eliminate waste orduplications in resource application.